The Effect of Donor Characteristics on the Survival in Patients Undergone Deceased Donor Liver Transplantation - Yilmaz, Mehmet; Akbulut, Sami; Eris, Cengiz; Karabulut, Koray; Yilmaz, Sezai (Wiley-Blackwell, 2012)
[Abstract Not Available]
18th Annual International Congress on ILTS -- MAY 16-19, 2012 -- San Francisco, CA